Effeciency of simulating decay heat in the corium of a nuclear reactor by the ohmic heating method - Skakov, M.K.; Baklanov, V.V.; Nurpaissova, G.S.; Toleubekov, K.O.; Akaev, A.S.; Bekmuldin, M.K. (Recent Contributions to Physics, 2024)
Most commonly, in consequence of a severe accident at a nuclear power plant (NPP) followed by a meltdown of the reactor core, corium is formed. Decay heat is one of the features of it and highly affects the thermal field of the entire corium. Thus, taking into account the decay heat is a central to physical modeling of severe accidents. For this reason, methods for simulating decay heat must meet at least two requirements of physical modeling: intensity and uniformity of heating throughout the entire volume of the melt. This paper provides studies on the efficiency of using ohmic heating as a method for simulating decay heat in a corium prototype during experiments at the LAVA-B test-bench. Melt heating data using an ohmic heater was obtained by computer modeling based on a software package ANSYS. To assess the efficiency of using ohmic heating, the obtained calculation parameters were compared with the parameters of other existing methods for simulating decay heat in the melt under similar conditions, such as induction heating and plasmatron heating.